Interaction between Islam and Hausa Culture After Sokoto Caliphate in Nigeria and The Role of Colonialists - Mukhtar Umar Dagimun (Ar-Raniry: International Journal of Islamic Studies, 2018)
Islam provides full guidance on all aspects of man’s life. It regulates the conduct of man to be in line with the tenets of the Shari’ah. Every community or tribe has its own customs, traditions, norms, and values that bind them together. In the same vein, Hausa people were identified with their set of traditions and culture since time immemorial. Some of these customs were worthy of commendation while others were blameworthy. With the coming of Islam in the land and the reforms brought by different agencies, groups, and individuals, Hausa culture was made to conform to the teachings of Islam. The Colonialists reached Hausa Land when Islam was firmly established. When they failed in the massive conversion of the Muslims to Christianity, they resorted to promoting some of the Hausa cultures which Islam condemned and prohibited. This paper seeks to examine how Islam interacted with these un-Islamic Hausa culture as promoted by the colonialists and Christian missionaries to counter its teachings